Information Security in Civil Aviation - R.B, Ahmetkaliev; T.A, Karimov; P.A, Kim; M.V, Kim (European Journal of Applied Sciences, 2018)
In this paper is considered Information Security in Civil Aviation. This is the more important topic. Because the Security of country dependens from Information Security in Civil Aviation.